Diferencias y convergencias entre el pragmatismo peirceano y otros pragmatismos - Reyes, Paniel (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2016)
The term “pragmatism” has been used and abused by doctrines that are even contradictory among them. For the founder of Pragmatism as a philosophicaltradition, Charles Peirce, this situation might seem a sad misunderstanding, and that is why he came up with the term “pragmaticism” in order to distinguish his own particular version of Pragmatism. However, Peirce himself did not leave a systematic treaty that explained what kind of specific conditions distinguish his pragmatism from other versions. In this essay I introduce some criteria that I deem fundamental to disambiguate the meaning of Pragmatism: (1) the use of the logical principle known as the ‘pragmatic maxim’, upon which the corner stone of the tradition should rest; (2) the need to adopt Scholastic Realism and reject Nominalism; and (3), the operationalist character (as opposed to the inferential character) of Peirce’s pragmatism. In addition, I offer some views avowing that in spite of the differences and distinctions that these criteria establish, there is a core of convergence between the different kinds of pragmatisms present in the philosophical tradition.

Distintas doctrinas, incluso contrapuestas entre sí, presumen de ser una forma de “pragmatismo”. Para el fundador del Pragmatismo en tanto tradición filosófica, Charles Peirce, esta situación puede resultar en una lamentable confusión y, por tanto, acuñó el término de ‘pragmaticismo’ para distinguir su particular versión.Sin embargo, Peirce mismo no escribió un texto sistemático en el que explicara qué criterios específicos distinguen su pragmatismo de cualquier otro. En este texto presento algunos de estos criterios que me parecen fundamentales: (1) el uso de una máxima pragmática sobre la cual ha de descansar el principio lógico que fundamenta la tradición, (2) La necesidad de adoptar el realismo escolástico y rechazar el nominalismo; y (3) El caracter operacionalista, opuesto al inferencialista, del pragmatismo de Peirce. Además, presento algunas opiniones que hacen pensar que a pesar de las distinciones que estos criterios establecen hay un núcleo de convergencia entre los distintos tipos de pragmatismos presentes en la tradición filosófica.
Keywords: Pragmatismo; Operacionalismo; Máxima pragmática; Charles Peirce; William James; https://purl.org/pe-repo/ocde/ford#6.03.01